Mean grain size as a function of spectral amplitude: a new regression law for marine sediment cores - Zanette, Nelly (Acta geotechnica Slovenica, 2006)
Geophysics has been developed in order to supply indicative estimations in soil mechanics like the grain size distribution of finely grained soils as day, silt and fine sands. The paper describes the attempt to characterize porous and saturated marine sediments with a non destructive technique which is the acoustic wave, in order to determine the correlation with geotechnical measurements. The characterization of physical parameters of marine sediments was based on research methods which permit to describe the parameters defining different types of sediment and zones of sedimentation; to determine fundamental parameters that influence the propagation of the acoustic waves in saturated and porous means; to define quick and indicative methods for characterization of physical parameters of analysed means. The acoustic measurements were carried out at SACLANT-NATO of La Spezia (I), where the Vertical Multi Sensor Core Logger (V-MSCL) was used. The results of acoustic tests were compared to the grain size curves of the sediments and the propagation characteristics such as velocity, density, porosity and absorption of experimentally determined data. The analyses are based 011 various mathematical models presented in. literature, in order to predict and to describe physical mechanisms of the wave propagation using a simplification of the sediment structure. The target of the study was to determine a new mathematical law that linked the mean grain size to a directly measurable parameter such as the spectral amplitude, and to offer the possibility to obtain the first indicative value of the sediment mean grain size. The determined exponential law represents an innovative and quick approach to determine a physical characteristic of saturated and porous sediments such as the grain size in a non destructive way based on the spectral analysis of the wave propagation form.
Keywords: analize; geomehanika; granulometrija; metode; morski sedimenti